2019
DOI: 10.1021/acs.jafc.9b06107
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Kokumi Substances and Bacteria in Thai Fermented Freshwater Fish (Pla-ra)

Abstract: A 16S rRNA next-generation sequencing technique was applied to investigate the microbial diversity and liquid chromatography–tandem mass spectrometry was used to identify glutamyl peptide profiles of 10 Thai fermented freshwater fish (Pla-ra) samples. A total of 12 genera of bacteria were able to be detected, with Tetragenococcus spp., Staphylococcus spp., and Lactobacillus spp. dominating. Of the 18 glutamyl peptides analyzed, 17 were found, even though the amounts detected were lower than the taste threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…The kokumi intensity of γ-Glu-Val-Gly is 12.8 times higher than that of GSH. Moreover, the addition of 0.01% γ-Glu-Val-Gly significantly increased the intensity of sweetness, saltiness, and umami of the food. , In nature, γ-Glu-Val-Gly is present in several foods such as scallops, fermented fish sauces, shrimp pastes, soy sauce, miso, and fermented fish …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The kokumi intensity of γ-Glu-Val-Gly is 12.8 times higher than that of GSH. Moreover, the addition of 0.01% γ-Glu-Val-Gly significantly increased the intensity of sweetness, saltiness, and umami of the food. , In nature, γ-Glu-Val-Gly is present in several foods such as scallops, fermented fish sauces, shrimp pastes, soy sauce, miso, and fermented fish …”
Section: Introductionmentioning
confidence: 97%
“…6,7 In nature, γ-Glu-Val-Gly is present in several foods 8 such as scallops, 9 fermented fish sauces, 10 shrimp pastes, 11 soy sauce, 12 miso, 13 and fermented fish. 14 We previously reported a method to produce kokumi seasoning by γ-glutamylation of gluten hydrolysate using Bacillus amyloliquefaciens γ-glutamyltranspeptidase (GGT; EC 2.3.2.2). 15 GGT catalyzes the hydrolysis of γ-glutamyl compounds and the transfer of their γ-glutamyl moieties to other amino acids and peptides.…”
Section: Introductionmentioning
confidence: 99%
“…These microbial community are also similar to the microbial profile in another fermented fishery product such as Korean salted and fermented seafood called Jeotgal (5, 6), salt-fermented shrimp paste (1) and anchovy sauce Budo (7). Even though the comparable trends of bacterial profiles were proposed, many environmental factors including raw materials, formulation, equipment and production process were highly affected microbial community dynamics during fermentation (2).…”
Section: Introductionmentioning
confidence: 56%
“…These bacteria have an important role in flavour characteristic of product attributed to their lipolytic and proteolytic activities (24, 27). A positive relationship between the presence of Virgibacillus and Tetragenococcus and the generation of glutamyl peptides responsible for taste enhancers of Pla-ra has been acknowledged (1). It was also reported that an increase of Staphylococcus was accompanied by the development of esters in relation with their high catalytic activity (4, 28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation